2021
DOI: 10.3389/fimmu.2021.670391
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytokines in Predicting the Response and Adverse Events Related to Immune Checkpoint Inhibitors

Abstract: Recently, the overall survival (OS) and progression-free survival (PFS) of patients with advanced cancer has been significantly improved due to the application of immune checkpoint inhibitors (ICIs). Low response rate and high occurrence of immune-related adverse events (irAEs) make urgently need for ideal predictive biomarkers to identity efficient population and guide treatment strategies. Cytokines are small soluble proteins with a wide range of biological activity that are secreted by activated immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 143 publications
(168 reference statements)
4
70
0
Order By: Relevance
“…Cytokines that are secreted by immune cells such as macrophages, activated T-cells, B-cells and NK cells take a lead in irAEs pathophysiology. Increased levels of IFN-γ and IFN-γ pathway genes are positive biomarkers of tumor response on ICI treatment and irAEs and IL-8, IL-6, and TGF-β are negative biomarkers ( 22 ). Experimental study evaluated cardiomyocyte cell line showed an increase of IL-1β, IL-8, IL-6, and TGF-β after Nivolumab and Ipilimumab affection ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines that are secreted by immune cells such as macrophages, activated T-cells, B-cells and NK cells take a lead in irAEs pathophysiology. Increased levels of IFN-γ and IFN-γ pathway genes are positive biomarkers of tumor response on ICI treatment and irAEs and IL-8, IL-6, and TGF-β are negative biomarkers ( 22 ). Experimental study evaluated cardiomyocyte cell line showed an increase of IL-1β, IL-8, IL-6, and TGF-β after Nivolumab and Ipilimumab affection ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…proposed [64][65][66] . Moreover, IL-1α blocking agents have already been tested in clinical trials on patients with various tumors and with different grading, showing variable efficiency 41,42,44,64 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the variability of cytokines levels and responses to cytokines-based therapies in patients 61 , IL-1α blockade could be envisaged as an alternative to IL-6 inhibition for boosting STAT3i 62 in those patients with low levels of IL-6 and low sensitivity to IL-6 depletion 63 . The specific cytokines expression profiling in patients, in fact, might be a useful tool to predict the patient response to the treatment and to design the best therapeutic strategy, according to the concept of personalized medicine, as previously proposed [64][65][66] . Moreover, IL-1α blocking agents have already been tested in clinical trials on patients with various tumors and with different grading, showing variable efficiency 41,42,44,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Candidate cytokine biomarkers for CRC include APRIL, BAFF, IL8 and MMP2, which are inversely correlated with immune cell infiltration and expression of CD163, a marker of M2 macrophages [ 203 ]. Another investigation revealed that IL-17A increased expression of PD-L1 on CRC cells and that inhibition of IL-17A improved the efficacy of anti-PD-1 therapy in a murine MSS CRC model [ 204 , 205 ]. Further investigation and validation is needed to translate use of these biomarkers into the clinic.…”
Section: Predictive Biomarkers For Response To It In Colorectal Cancermentioning
confidence: 99%